2011
DOI: 10.2178/jsl/1294171002
|View full text |Cite
|
Sign up to set email alerts
|

On the non-confluence of cut-elimination

Abstract: We study cut-elimination in first-order classical logic. We construct a sequence of polynomial-length proofs having a non-elementary number of different cut-free normal forms. These normal forms are different in a strong sense: they not only represent different Herbrand-disjunctions but also differ in their prepositional structure.This result illustrates that the constructive content of a proof in classical logic is not uniquely determined but rather depends on the chosen method for extracting it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…For example, if one tries to enrich the usual CCC semantics for intuitionistic logic with an involutive negation, then the CCC degenerates into a poset that equates all proofs of a formula (Joyal's paradox) [25]. In terms of the sequent calculus, this problem manifests as follows: cut-elimination using Gentzen's cut-reduction rules is neither confluent nor strongly normalizing for LK proofs [13,3,19]. To force confluence, for instance, one would have to equate all cut-free proofs of a formula which again trivializes the semantics.…”
Section: Related Workmentioning
confidence: 99%
“…For example, if one tries to enrich the usual CCC semantics for intuitionistic logic with an involutive negation, then the CCC degenerates into a poset that equates all proofs of a formula (Joyal's paradox) [25]. In terms of the sequent calculus, this problem manifests as follows: cut-elimination using Gentzen's cut-reduction rules is neither confluent nor strongly normalizing for LK proofs [13,3,19]. To force confluence, for instance, one would have to equate all cut-free proofs of a formula which again trivializes the semantics.…”
Section: Related Workmentioning
confidence: 99%
“…The large normal forms of acyclic proofs are therefore only due to repetitions of the same formulas and thus mathematically meaningless. The analogous question for cyclic proofs is open: it has been shown in [1] that a (cyclic) proof can have a non-elementary number of reachable Herbranddisjunctions. It is unclear however whether there exists a (cyclic) proof having infinitely many reachable Herbrand-disjunctions.…”
Section: Lemma 10 Every Directed Proof Is Acyclicmentioning
confidence: 99%
“…Each restriction of the full set of proof rewrite rules has the (sometimes intended) effect of limiting the obtainable results. However, recent work [1] has shown that the number of (significantly different) normal forms may increase non-elementarily in the size of the original proof. An investigation of cut-elimination as non-deterministic computation can be found in [37,38], including a case study of a non-confluent proof in [37].…”
Section: Introductionmentioning
confidence: 99%
“…Note that we do not impose any restriction on the strategy that can be applied. Therefore this set of reduction rules is not confluent, see [4] for a strongly non-confluent example. It is also not strongly normalising by allowing the doublecontraction example found e.g.…”
Section: Cut-eliminationmentioning
confidence: 99%
“…[7,23], to be used as a programming language this effect is intended. However, from the foundational point of view that asks for the constructive content of a mathematical proof in classical logic it has the unfortunate consequence of strongly reducing the degree of generality in which the original proof is considered, see [4].…”
Section: Cut-eliminationmentioning
confidence: 99%